Between tourist and traveller; The Reverend Marius Buys in the Preanger (1887-1890) - Sunjayadi, Achmad (Wacana, Journal of the Humanities of Indonesia, 2024)
This article presents the postcolonial analysis of the travel account and guidebook of Marius Buys (1837-1906), a Dutch clergyman. He not only devoted himself as a priest but also travelled in several parts of the Dutch East Indies, such as Java, Sumatra, and Sulawesi in the years 1878-1885. After returning to the Netherlands due to illness in 1885, he returned to the Indies in 1886 and was assigned to Kalimantan, Sumatra, and Java. In May 1887 he posted in Bandung West Java (the Preanger regencies), where he remained until his return to the Netherlands in 1890. As a result of his serving in the Preanger regencies (1878-1890), Marius Buys published Batavia, Buitenzorg en de Preanger. Gids voor Bezoekers en Toeristen (1891), the travel guidebook for travellers and tourists. His experiences in Preanger were also recorded in his travel account In het hart der Preanger (1900). The clergyman’s perspective as a tourist and traveller for the indigenous peoples and colony in his travel text and guide book are analysed by using the concepts of Esme Cleall (2012) about European missionaries thinking in British empire in Asia and Africa in the nineteenth century.